2020
DOI: 10.21037/atm.2020.01.89
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vertical sleeve gastrectomy, long and short-term impact on weight loss and associated co-morbidities

Abstract: The laparoscopic vertical sleeve gastrectomy (LVSG) has become the most popular operation for the treatment of morbid obesity in the United States. Being a purely restrictive procedure, the LVSG works to reduce the caloric intake of patients as well as decrease appetite through removal of ghrelin producing cells. Initially developed as the first part of a combined two step restrictive and malabsorptive procedure, the LVSG developed as a standalone procedure when patients lost significant weight with the restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
9
0
3
Order By: Relevance
“…The introduction of the laparoscopic vertical sleeve gastrectomy (LVSG) has seen a marked rise in usage, even overtaking Rouxen-Y Gastric Bypass (RYGB) (23,24); in fact, it has become the most popular operation for the treatment of morbid obesity in the United States and worldwide due to its technical simplicity and palatability to patients (25,26).…”
Section: Vertical Gastrectomy or Gastric Sleevementioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of the laparoscopic vertical sleeve gastrectomy (LVSG) has seen a marked rise in usage, even overtaking Rouxen-Y Gastric Bypass (RYGB) (23,24); in fact, it has become the most popular operation for the treatment of morbid obesity in the United States and worldwide due to its technical simplicity and palatability to patients (25,26).…”
Section: Vertical Gastrectomy or Gastric Sleevementioning
confidence: 99%
“…LVSG also causes physical loss of principal producer of ghrelin, classically attributed to the fundus gastric (28). Being a purely restrictive procedure, the LVSG works to reduce the caloric intake of patients and decrease appetite through removal of ghrelin producing cells (25).…”
Section: Vertical Gastrectomy or Gastric Sleevementioning
confidence: 99%
See 1 more Smart Citation
“…While some reviews show similar %EWL with SG and RYGB at short and long-term [43], other reviews show better results with RYGB [44], with a greater treatment failure after six years for SG [44]. Most of the studies demonstrated and maintained weight loss through follow-up at five years and even for longer intervals (up to 11 years) [43]. However, a slow weight gain between the second and third years of postsurgery follow-up is found, increasing up to 5 years postsurgery [45].…”
Section: Discussionmentioning
confidence: 96%
“…Studies for short-and long-term weight-loss show different results. While some reviews show similar %EWL with SG and RYGB at short and long-term [43], other reviews show better results with RYGB [44], with a greater treatment failure after six years for SG [44]. Most of the studies demonstrated and maintained weight loss through follow-up at five years and even for longer intervals (up to 11 years) [43].…”
Section: Discussionmentioning
confidence: 99%